ANALYSIS OF PERIODONTALLY COMPROMISED PATIENTS UNDERGOING TREATMENT ONLY FOR SUBGINGIVAL SCALING WITH OR WITHOUT PERIODONTAL FLAP SURGERY - Ahmad Fauzi, Nur Qistina Binti; Ramamurthy, Jaiganesh; Gurunathan, Deepa; Gurunathan, Deepa; Gurunathan, Deepa; Ramamurthy, Jaiganesh (International Journal of Psychosocial Rehabilitation, 2019)
The most important part in a periodontal therapy is the ability to completely remove the calculus from the tooth structure. In some cases, even after the completion of the periodontal therapy, a significant amount of calculus can still be present. With that in mind, the formation of a proper treatment plan should be based upon the patient’s periodontal status would ultimately provide a better prognosis in the future. The aim of the study is to analyse periodontally compromised patients that are opting for subgingival scaling with or without periodontal flap surgery. The sample size consists of 164 patients who were diagnosed with chronic periodontitis. Each patient’s gender, age, periodontal status as well as treatment records was obtained through patient records from the institution between June 2019 to March 2020. Based on the severity of the periodontal disease, patients with highly severe periodontal status commonly undergo both subgingival scaling and flap surgery (55.8%) compared to patients with less severe periodontal status opting only for subgingival scaling only (44.2%). Chi square test was one and there was a positive correlation between the mean attachment loss (mm) of the patient and the treatment being done (p=0.00).Within the limits of our study, it was found that the severity of the periodontal disease determines the treatment option of the patients. Patients undergoing both subgingival scaling and flap surgery are more commonly associated with more severe periodontal status while those opting for only subgingival scaling have a less severe periodontal status.